2007
DOI: 10.1007/s10552-007-9008-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in factors associated with smoking initiation

Abstract: We sought to determine whether the influence of two factors known to influence smoking initiation (parental smoking and lower academic attainment) vary by age of smoking initiation and to develop profiles of smokers based on their age of smoking initiation. We analyzed data on demographic and smoking characteristics from 1,447 former and current cancer-free smokers, born between 1912 and 1975, who served as controls in an ongoing lung cancer case-control study, and who reported initiating smoking before their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
3
18
1
1
Order By: Relevance
“…Prior studies based in Europe and several studies based in the United States, Iran, Thailand, and Mexico found that friends and family exert a strong influence on a woman's decision to start smoking (32)(33)(34)(35)(36). However, parent smoking was not associated with knowledge and beliefs about smoking in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Prior studies based in Europe and several studies based in the United States, Iran, Thailand, and Mexico found that friends and family exert a strong influence on a woman's decision to start smoking (32)(33)(34)(35)(36). However, parent smoking was not associated with knowledge and beliefs about smoking in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Accordingly, a greater degree of nicotine-induced excitability in cholinergic LDT neurons demonstrated in the present study could play a part in the higher susceptibility to nicotine addiction seen in younger individuals. It will be of interest to determine whether the decrease in nicotinic-mediated cholinergic cellular excitability noted in the ranges of ages examined demonstrates the same trajectory across a larger range of ontogenetic periods, which may explain why initiation of smoking at an early age is associated with a high risk of development of nicotine dependence, whereas exposure to nicotine at older ages is less likely to lead to addiction (Chen and Millar, 1998; Kendler et al, 2013; Wilkinson et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Parental, sibling, and friend smoking all have been shown to be strongly associated with an individual's smoking status [6-13]. Low academic achievement as well as low socioeconomic status are also associated with smoking status [8,12,14-16]. Women, just like men, begin to smoke in increasing proportions in the population because of marketing [17] and the tobacco industry significantly targets women with focused advertisements and promotions [18].…”
Section: Introductionmentioning
confidence: 99%